2017
DOI: 10.1016/j.jnci.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral proptosis as the initial manifestation of malignancy

Abstract: Proptosis, a common sign with a broad differential diagnosis, is defined as anterior displacement and protrusion of one or both orbital globes. Patients can present with varying degrees of chronicity, visual loss and associated symptoms. The etiology of acquired unilateral proptosis is diverse, ranging from benign to life-threatening. The causes of unilateral proptosis include traumatic, vascular, endocrine, inflammatory, infective and malignant. Breast carcinoma is the most common metastatic cause of proptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…Pyroptosis has been confirmed as an important mechanism for cell growth inhibition. 20 In the current research, cell pyroptosis was Pathway of pyroptosis has been found to be mostly modulated by the interaction with members of the NLRP3 and GSDMD protein family. 21 When the expression of NLRP3 and GSDMD was The apoptosis of BC cells was measured by flow cytometry.…”
Section: Discussionmentioning
confidence: 80%
“…Pyroptosis has been confirmed as an important mechanism for cell growth inhibition. 20 In the current research, cell pyroptosis was Pathway of pyroptosis has been found to be mostly modulated by the interaction with members of the NLRP3 and GSDMD protein family. 21 When the expression of NLRP3 and GSDMD was The apoptosis of BC cells was measured by flow cytometry.…”
Section: Discussionmentioning
confidence: 80%
“…Chronic proptosis occurs in diseases, such as fibrous dysplasia, and tumours, such as dermoid cysts, lymphomas, benign mixed tumours, neurogenic and vascular tumours, and osteomas. 5,21…”
Section: Classification Based On Onsetmentioning
confidence: 99%
“…P roptosis is described as an abnormal protrusion of the eyeball, reflecting an increase in orbital volume (1) . The causes of unilateral proptosis include trauma, endocrine ophthalmopathy, inflammatory disease like orbital cellulitis, tumour, including orbital haemangioma, malignant lymphomas and metastatic malignant tumours (1,2) . Sinonasal undifferentiated carcinoma (SNUC) is a rare and extremely aggressive malignancy.…”
Section: Introductionmentioning
confidence: 99%